ANALYSIS OF FINANCIAL PERFORMANCE ON THE PREDICTION OF FINANCIAL DISTRESS IN THE INDONESIA STOCK EXCHANGE - Nuryani, Ni Nyoman Juli (Jurnal Pendidikan Ekonomi (JURKAMI), 2023)
This study aims to determine the effect of liquidity ratios, profitability ratios, economic profitability ratios and leverage ratios on the prediction of financial distress in the banking sector on the Indonesia Stock Exchange. This study uses a quantitative approach. The sample used is data on the banking sector that has gone public with a total of 10 banks for the 2020-2022 period. The analysis technique used in this study is the classical assumption test, multiple linear regression analysis of determination analysis and hypothesis testing with the T-Test and F-Test. The results of the study show that the Liquidity Ratio, Profitability Ratio, Earnings Ratio and Leverage Ratio affect the Prediction of Financial Distress of banking companies on the Indonesia Stock Exchange by 78.3% and the remaining 21.7% is influenced by other factors not examined in this study. The profitability ratio is the ratio that has the most dominant influence on the prediction of a company's Financial Distress